2012
DOI: 10.4238/2012.august.13.5
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletion on 17p11.2 in a Smith-Magenis syndrome patient with mental retardation and congenital heart defect: first report from China

Abstract: ABSTRACT. Smith-Magenis syndrome (SMS) is a rare syndrome with multiple congenital malformations, including development and mental retardation, behavioral problems and a distinct facial appearance. SMS is caused by haploinsufficiency of RAI1 (deletion or mutation of RAI1). We describe an eight-year-old female Chinese patient with multiple malformations, congenital heart defect, mental retardation, and behavioral problems (self hugging, sleeping disturbance). High-resolution genome wide single nucleotide polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Pulmonary atresia has been previously reported in two studies (Wong et al, 2003; Yamamoto et al, 2006). The most frequent CHD is TOF (C. Huang et al, 2012; Li et al, 2015; Sweeney et al, 1999; Thomas et al, 2000; Yamamoto et al, 2006). More complex CHD have been described such as the association of atrioventricular canal defect, mild left pulmonary artery hypoplasia, small patent ductus arteriosus (PDA) and PAPVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary atresia has been previously reported in two studies (Wong et al, 2003; Yamamoto et al, 2006). The most frequent CHD is TOF (C. Huang et al, 2012; Li et al, 2015; Sweeney et al, 1999; Thomas et al, 2000; Yamamoto et al, 2006). More complex CHD have been described such as the association of atrioventricular canal defect, mild left pulmonary artery hypoplasia, small patent ductus arteriosus (PDA) and PAPVC.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the great variability of cardiac defects in SMS, an extensive literature search showed VSD (Abuelo & Corwin, 1993; Chaudhry et al, 2007; Wong et al, 2003), TOF (Huang et al, 2012; Li et al, 2015; Myers & Challman, 2004; Sweeney et al, 1999), ASD (Abuelo & Corwin, 1993; Chaudhry et al, 2007; Huang et al, 2012), and TAPVC (Myers & Challman, 2004) as those more frequently reported, occurring as isolated, in association with one another or with other cardiac structural defects.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 The gene functions of RAI1 are linked to regulation of several genes that control specific pathways of various biological processes. 7 This syndrome was first described by Smith et al in 1982, in 2 patients with cleft palate and congenital heart disease. 8 There have been a number of reports describing various skeletal features in this syndrome, including brachydactyly, short stature, cleft lip/palate, persistent fetal finger pads, and polydactyly.…”
Section: Introductionmentioning
confidence: 97%
“…About 64% of individuals with 22q11.2 deletion syndrome have heart defects and > 90% are de novo34,35 .One individual with craniofacial anomalies, supravalvar aortic stenosis, atrial septal defect and DD, carrying a de novo 1.42 Mb deletion at 7q11.23 including ELN (130160) and 31 other genes, was diagnosed with Williams-Beuren syndrome, which is well-known and another common recognizable syndrome in CHD cohorts 36 . Other rare chromosome syndromes identi ed in this cohort included Smith-Magenis syndrome in an individual with TOF and DD (de novo deletion of 3.53 Mb at 17p11.2)37 ; a 1-month-12-day boy with feeding problems, mild dysmorphic features, CAVCD and DD with Langer-Giedion syndrome (de novo deletion of 14.2 Mb at 8q24.11q24.22) 38 ; a male patient with PA, VSD and DD harboring a 846 kb deletion at 3p26.3 consistent with 3p deletion syndrome 39 ; one 51.9 Mb partial trisomy at 11q14.1q25 in a 6-month girl with atrial septal defect, dysmorphic features, and dislocation of hip joint, matching 11q partial trisomy syndrome40,41 .Interestingly, we detected 3 rare de novo CNVs at chromosome 7 in one 3-month boy with complex phenotypes of multiple systems such as VSD, ASD, pulmonary arterial hypertension, tricuspid regurgitation, agenesis of corpus callosum, scoliosis, microphallus, hypotonia, hypospadias, and DD. The 3 CNVs include a 1.8 Mb deletion at 7p22.3 encompassing 36 genes and a major OMIM gene of FAM20C (#611060).…”
mentioning
confidence: 99%